Views and experiences of managing eczema: systematic review and thematic synthesis of qualitative studies. (14th August 2020) - Teasdale, E.; Muller, I.; Sivyer, K.; Ghio, D.; Greenwell, K.; Wilczynska, S.; Roberts, A.; Ridd, M.J.; Francis, N.; Yardley, L.; Thomas, K.S.; Santer, M.
Summary: Background: The number of qualitative studies on eczema has increased rapidly in recent years. Systematically reviewing these can provide greater understandings of people's perceptions of eczema and eczema treatments. Objectives: We sought to systematically review and thematically synthesize qualitative studies exploring views and experiences of people with eczema and parents/carers of children with eczema. Methods: We searched MEDLINE, EMBASE, PsycINFO and CINAHL from the earliest date available to February 2019. We selected papers focusing on views and experiences of eczema and eczema treatments, and barriers/facilitators to eczema self‐management. We excluded papers focusing on health service provision models or health professionals' views. Results: We synthesized 39 papers (reporting 32 studies) from 13 countries. We developed four analytical themes: (1) Eczema not viewed as a long‐term condition; (2) Significant psychosocial impact not acknowledged by others; (3) Hesitancy (patient/carer uncertainty) about eczema treatments; and (4) Insufficient information and advice. Our findings suggest that people with eczema and their carers experience frustration at having to manage a condition that is often seen by others as mundane but has significant psychosocial impact and is difficult to manage due to concerns about, and burden of, treatment. This frustration can be exacerbated by experiences of conflicting and/or insufficient information and advice from health professionals, family and others. Conclusions: Effective self‐management of eczema could be supported by addressing beliefs and concerns about treatments; seeking positive ways to promote a 'control not cure' message; acknowledging psychosocial impacts of eczema and treatment burden; and providing clear consistent advice or signposting towards reliable information. Abstract : What is already known about this topic? Eczema is a common skin condition that can have a substantial impact on quality of life. One of the most common causes of treatment failure in mild‐to‐moderate eczema is the underuse of topical treatments. Increasingly, qualitative approaches have been adopted to understand people's views and experiences of eczema and eczema treatment, which can help to address common barriers and support effective self‐management. What does this study add? We found a large volume of qualitative studies giving valuable insights into people's perceptions of eczema. Synthesizing these studies highlights many recurring themes and adds further insights, for instance different perceptions between adults with eczema and parents of children with eczema on its long‐term nature. Eczema can be difficult to manage due to treatment hesitancy and burden and misperceptions about the long‐term nature of eczema. Hesitancy or concern about eczema treatments is made worse by insufficient and inconsistent information and advice. What are the clinical implications of the work? Health professionals need to address common treatment beliefs and concerns and seek positive ways to promote a 'control not cure' message to support effective ongoing self‐management. Acknowledging the significant psychosocial impacts of eczema and burdensome nature of treatment and providing clear consistent information and advice or signposting towards credible information may address people's concerns that distress caused by the condition is not taken seriously. Linked Comment: Capozza. Br J Dermatol 2021; 184 :587–588 .